Achromobacter xylosoxidans as emerging pathogen in healthcare settings: A mini review - Galo Farfán-Cano; Glen A. Silva-Rojas (Narra X, 2023)
Microorganisms of the genus Achromobacter have been mentioned as a cause of opportunistic infections, mainly in patients with cystic fibrosis or pulmonary lymphoma, with the species Achromobacter xylosoxidans being identified to a large extent. A. xylosoxidans was first described in 1971 and is an opportunistic pathogen. However, it been reported to cause chronic purulent otitis, meningitis, pneumonia, peritonitis and urinary tract infections, chronic obstructive pulmonary disease and other infections. The present literature review aims to analyze and synthesize the state of the art on A. xylosoxidans and its potential as an emerging pathogen in the healthcare settings. We discuss A. xylosoxidans as an emerging opportunistic pathogen that is associated with healthcare infections. This review further discusses the prevalence of A. xylosoxidans in healthcare settings, the types of infections it can cause, and the risk factors for acquiring an A. xylosoxidans infection. The review also covers the challenges in treating A. xylosoxidans infections, including its potential for drug resistance and the lack of specific treatments. Strategies for preventing and controlling A. xylosoxidans infections in healthcare settings were also discussed.